How do you solve lnx=-1? Precalculus Solving Exponential and Logarithmic Equations Logarithmic Models 1 Answer sjc Jan 26, 2017 1/e Explanation: lnx=-1=>log_(e)x=-1 =>e^(-1)=x :.x=1/e Answer link Related questions What is a logarithmic model? How do I use a logarithmic model to solve applications? What is the advantage of a logarithmic model? How does the Richter scale measure magnitude? What is the range of the Richter scale? How do you solve 9^(x-4)=81? How do you solve logx+log(x+15)=2? How do you solve the equation 2 log4(x + 7)-log4(16) = 2? How do you solve 2 log x^4 = 16? How do you solve 2+log_3(2x+5)-log_3x=4? See all questions in Logarithmic Models Impact of this question 140372 views around the world You can reuse this answer Creative Commons License